Comparison of Proliferation and Apoptosis in CD34+ Lymphoblasts in Pediatric Acute Lymphoblastic Leukemia: invivo and exvivo Conditions - Hernaningsih, Yetti; Cahyadi, Andi; Rusanti, Rahmi; Armayani, Erawati; Juwita, Syntia Tanu; Nur‘ Aini, Farida; Tanzilia, May Fanny; Nunki, Nastasya (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
The proliferation and apoptosis assays have been utilized in numerous studies to develop new substances such as antineoplastic agents. Commonly, it was performed in ex-vivo conditions using the culture method. However, the cytotoxic or cytostatic effects observed ex vivo often differ from those in vivo. This study investigated differences in proliferation and apoptosis of lymphoblast between in vivo and ex vivo conditions of childhood ALL. This study was conducted on new childhood acute lymphoblastic leukemia (ALL) patients. Nineteen (19) subjects were recruited, comprising of 10 with favorable and 9 with unfavorable outcomes. The negative control came from 8 healthy children volunteers. All patients under went leukemia immunophenotyping, including CD34, to identify the phenotype. Bone marrow mononuclear cells (BMMCs) of patient groups were analyzed using apoptosis and proliferation assays, as well as the negative control group, and then compared to the in vivo condition. 12 out of 19 BMMC were cultured for 48 hours, and proliferation and apoptosis assays were performed in ex vivo conditions. The results showed that the proliferation, apoptosis, and apoptosis/proliferation (A/P) ratio of the patients in the ex vivo group were significantly higher than the in vivo group with p =0.000, p =0.050, and p =0.000, respectively. The proliferation was higher for patient groups than the control group, with p =0.001 and p =0.004, respectively. The apoptosis rates of the patient group were higher than the control group, with p =0.000 and p =0.002, respectively. The proliferation and apoptosis of lymphoblasts ex vivo are higher than in vivo.